2011
DOI: 10.5047/eps.2011.07.013
|View full text |Cite
|
Sign up to set email alerts
|

P n tomographic velocity and anisotropy beneath the Tibetan Plateau and the adjacent regions

Abstract: We present a tomographic velocity and anisotropy model of the uppermost mantle beneath the Tibetan Plateau and the adjacent regions. The investigation analyzed 105,385 P n phase readings from the International Seismological Centre (ISC) and the China Earthquake Data Center. The average P n velocity under the study area is approximately 8.15 km/s, with velocity perturbations up to 3-4%. We find high P n velocities under the Indian Plate and in the Tarim and Sichuan basins, low P n velocities under the Hindu Kus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
4
4
0
Order By: Relevance
“…The upper-mantle velocities above 200 km beneath the Qiangtang and Songpan-Garzê Terranes are lower than in its north and south, especially beneath the Songpan-Garzê Terrane where a low-velocity zone exists (Figure 14). These results agree with previous Sn and Pn studies that showed a region of inefficient Sn propagation and low Pn velocities in northern-central Tibet (Lü Y et al, 2011). Cenozoic volcanism has also been discovered in this region (Gansser, 1980).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The upper-mantle velocities above 200 km beneath the Qiangtang and Songpan-Garzê Terranes are lower than in its north and south, especially beneath the Songpan-Garzê Terrane where a low-velocity zone exists (Figure 14). These results agree with previous Sn and Pn studies that showed a region of inefficient Sn propagation and low Pn velocities in northern-central Tibet (Lü Y et al, 2011). Cenozoic volcanism has also been discovered in this region (Gansser, 1980).…”
Section: Discussionsupporting
confidence: 93%
“…Travel‐time tomography studies suggested a high‐velocity anomaly down to 250–300 km beneath India (Huang JL and Zhao DP, ; Li C et al, ; Zhang H et al, ). A thick high‐velocity upper mantle lid has also been suggested by Lyon‐Caen () using SH‐wave triplication between 10° and 30°. Pn travel‐time studies have shown that the Pn velocity beneath India is 8.40 km/s (Hearn et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These are consistent with the previous Pn tomographic results in this region (McNamara et al, 1997;Pei et al, 2011;Lü et al, 2011;Feng and Pei, 2012). Local and regional 3-D tomographic results showed obvious low-velocity anomalies beneath the Pamir and Hindu Kush regions, which may extend down to 130 km depth (Lei et al, 2002;Koulakov and Sobolev, 2006;Negredo et al, 2007;Huang and Zhao, 2006 (Sippl et al, 2013;Lou et al, 2007;Van der Voo et al, 1999).…”
Section: The Western Tienshan and Pamirsupporting
confidence: 92%
“…The east-west variability of the S n velocity beneath southern Tibet indicates that the underthrusted Indian continental lithosphere is not a homogeneous body but rather in a piecewise manner. This conjecture is consistent with those of other researchers (Lü et al, 2011;Liang et al, 2012). A high S n velocity is found in the Tarim and Sichuan Basins, which have a cold lithosphere and stable tectonics.…”
Section: Resultssupporting
confidence: 93%
“…The tectonics of this area is active and has a complex structure, and is one of the hotspots of Earth science research (Molnar and Tapponnier, 1975;Teng et al, 1994Teng et al, , 1999Zeng et al, 2000;Zhang and Klemperer, 2010;Zhang et al, 2010aZhang et al, , b, 2011. This subject was the focus of a number of previous studies (Kind et al, 2002;Ding et al, 2003;Hearn et al, 2004;Liang et al, 2004;Zhao, 2004;Liang and Song, 2006;Pei et al, 2007Pei et al, , 2011aPhillips et al, 2007;Xu et al, 2007;Ren and Shen, 2008;Sun et al, 2008;Lü et al, 2011;Yue et al, 2012). The P n velocity inversion indicates that the Indian plate has a relatively high P n velocity, whereas areas in Afghanistan, Myanmar, and the Tibetan Plateau are low P n velocity zones.…”
Section: Introductionmentioning
confidence: 99%